2021
DOI: 10.21037/jgo-21-159
|View full text |Cite
|
Sign up to set email alerts
|

Microwave ablation for colorectal cancer metastasis to the liver: a single-center retrospective analysis

Abstract: The purpose of this study is to evaluate the safety and intermediate-term efficacy of percutaneous microwave (MW) ablation for the treatment of colorectal liver metastases (CRLM) at a single institution. Methods:A retrospective review was performed of all CRLM treated with MW ablation from 3/2011 to 7/2020 (102 tumors; 72 procedures; 57 patients). Mean age was 60 years (range, 36-88) and mean tumor size was 1.8 cm (range, 0.5-5.0 cm). The patient population included 19 patients with extra-hepatic disease. Chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…of patients No. of tumors Size of Tumors [mm] Follow-up [months] Local tumor control [%] Overall survival [months] Overall survival [%] (Disease- or Progression-free survival [%]) 1-year 2-year 3-year 4-year 5-year Cheng et al [ 11 ] 2021 RFA 68 29 (median) 59.8 (median) 47.1 53.4 (median) 88.1 66.9 64.5 Knott et al [ 12 ] 2021 MWA 57 102 18 (mean) 42 (median) 96 52 (median) 96 (93) 66 (58) 47 (39) Fan et al [ 13 ] 2021 RFA 199 402 16 (mean) 23 (median) 62.9 Subcapsular 46 (median) 96.1 66 44.2 non-subcapsular 60 (median) Kurilova et al [ …”
Section: Results In Each Type Of Primary Tumormentioning
confidence: 99%
See 1 more Smart Citation
“…of patients No. of tumors Size of Tumors [mm] Follow-up [months] Local tumor control [%] Overall survival [months] Overall survival [%] (Disease- or Progression-free survival [%]) 1-year 2-year 3-year 4-year 5-year Cheng et al [ 11 ] 2021 RFA 68 29 (median) 59.8 (median) 47.1 53.4 (median) 88.1 66.9 64.5 Knott et al [ 12 ] 2021 MWA 57 102 18 (mean) 42 (median) 96 52 (median) 96 (93) 66 (58) 47 (39) Fan et al [ 13 ] 2021 RFA 199 402 16 (mean) 23 (median) 62.9 Subcapsular 46 (median) 96.1 66 44.2 non-subcapsular 60 (median) Kurilova et al [ …”
Section: Results In Each Type Of Primary Tumormentioning
confidence: 99%
“…Cheng et al reported the outcome of RFA using a multielectrode radiofrequency switching controller for resectable metachronous CRLM; the 5-year survival and median OS were 50.7% and 53.4 months, respectively [11]. Table 2 presents the outcomes of RFA and MWA for CRLM including the 5-year OS rates [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. In the listed studies, 5-year OS following ablation ranged from 21 to 65%.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…26 A systematic review of the literature on RFA for CRC liver metastases reported a wide range of 5-year survival (14–55%) and local recurrence rates (3.6–60%). 27…”
Section: Ablative Therapies For Metastatic Colorectal Cancer To the L...mentioning
confidence: 99%
“…Microwave ablation (MWA) is a promising non-vascular interventional technique, with clear efficacy in local control. For the treatment of small primary and secondary hepatic tumors (<3 cm), MWA may be comparable to surgical resection (1)(2)(3)(4). Furthermore, numerous clinical trials have indicated that trans-arterial chemoembolization (TACE) combined with MWA may significantly improve the rate of complete necrosis of tumors and prolong the survival of patients (5,6).…”
Section: Introductionmentioning
confidence: 99%